The Citizenship Engagement Quality in ASEANand the Sustainability of ASEAN Economic Community Performance - Dwi Suseno, Bambang; Ali Yusuf, Furtasan; Pawirosumarto, Suharno (International Journal of Psychosocial Rehabilitation, 2020)
In the long run, ASEAN Economic Community Performance (AEC) is located in the future of prospective leaders, namely students in this region who are now studying in colleges. Data shows that the population in ASEAN with a total of 625 million, of which 125 million engaged in higher education which is distributed to 7,446 universities in 10 ASEAN countries (UNESCO, 2018). The purpose of this study is to (1) analyze regional dynamic influence to AEC; (2) empirically test regional dynamic influence on citizenship engagement; (3) analyze regional dynamic influence on risk of conflict; (4) analyze the influence of risk conflict on AEC performance; (6) empirically analyze the influence of citizenship engagement on AEC performance. As a framework to discuss the research problems, this study proposes the novelty of Citizenship Engagement Quality. The population in this research is the students from 10 ASEAN countries. Respondents in this research consist of 881 samples. Based on their status, the majority of the respondents are studying in undergraduate program with 765 respondents (86.8%) and postgraduate program as 116 respondents (13.2%). The majority of origin country is from Indonesia as 344 respondents (39.1%) as a larger population of students, Malaysia as 203 respondents (23,04 %) Burma as 67 respondents (7.60%), Laos as 62 respondents (7.03%), Brunei as 54 respondents (6.12%), Philippines as 47 respondents (5.33%), Singapore as 36 respondents (4.08%) and Vietnam and Thailand 34 respondents each (3.85% and 3.85%). Structural Equation Modeling is used in this study as data analyses tool by using IBM AMOS version 22.0. The result from empirical model testing hypothesis testing shows that correlative estimation value among latent variables (Regional dynamics, Citizen Engagement Quality, Risk of Conflict and AEC Performance) has significant correlative value. Critical ratio (CR) value is >1.96 and p-value is <0.05.